Design and Synthesis of Highly Active Antimycobacterial Mutual Esters of 2-(2-Isonicotinoylhydrazineylidene)propanoic Acid - Pflégr, Václav; Maixnerová, Jana; Stolaříková, Jiřina; Pál, Adrián; Korduláková, Jana; Trejtnar, František; Vinšová, Jarmila; Krátký, Martin (Pharmaceuticals (Basel, Switzerland), 2021)
The combination of two active scaffolds into one molecule represents a proven approach in drug design to overcome microbial drug resistance. We designed and synthesized more lipophilic esters of 2-(2-isonicotinoylhydrazineylidene)propanoic acid, obtained from antitubercular drug isoniazid, with various alcohols, phenols and thiols, including several drugs, using carbodiimide-mediated coupling. Nineteen new esters were evaluated as potential antimycobacterial agents against drug-sensitive Mycobacterium tuberculosis (Mtb.) H37Rv, Mycobacterium avium and Mycobacterium kansasii. Selected derivatives were also tested for inhibition of multidrug-resistant (MDR) Mtb., and their mechanism of action was investigated. The esters exhibited high activity against Mtb. (minimum inhibitory concentrations, MIC, from ≤0.125 μM), M. kansasii, M. avium as well as MDR strains (MIC from 0.25, 32 and 8 µM, respectively). The most active mutual derivatives were derived from 4-chloro/phenoxy-phenols, triclosan, quinolin-8-ol, naphthols and terpene alcohols. The experiments identified enoyl-acyl carrier protein reductase (InhA), and thus mycobacterial cell wall biosynthesis, as the main target of the molecules that are activated by KatG, but for some compounds can also be expected adjunctive mechanism(s). Generally, the mutual esters have also avoided cytotoxicity and are promising hits for the discovery of antimycobacterial drugs with improved properties compared to parent isoniazid.
Keywords: enzyme inhibition; esters; isoniazid; antimycobacterial activity; mutual prodrugs; mechanism of action; InhA